Three-dimensional computational fluid dynamic analysis of a large-scale vertical axis wind turbine. Issue 2 (April 2022) - Hand, Brian
The vertical axis wind turbine (VAWT) configuration has many advantages for an offshore wind turbine Installation. In this paper, the three dimensional (3D) computational fluid dynamics analysis of a large-scale 5 MW VAWT is conducted. At the optimum tip-speed ratio (TSR), the VAWT maximum inline force was 75% larger than the maximum lateral force. It was found the dynamic stall effects cause the VAWT flow field to become increasingly asymmetrical at the mid-span plane, when the TSR is reduced. The attachment of end plates to the blade tips, resulted in a performance improvement during the upwind phase with the average blade torque coefficient in this range being increased by 4.71%. Conversely, during the blade downwind phase a reduction in performance was found due to the increase in drag from the end plates and the average blade torque coefficient in this phase was reduced by 23.1%.